Low root PIP1-1 and PIP2 aquaporins expression could be related to reduced hydration in 'Rangpur' lime plants exposed to aluminium - Cavalheiro, Mariana F. [UNESP]; Gavassi, Marina A. [UNESP]; Silva, Giselle S. [UNESP]; Nogueira, Matheus A. [UNESP]; Silva, Carolina M. S.; Domingues, Douglas S. [UNESP]; Habermann, Gustavo [UNESP] (CSIRO Publishing, 2020)
In acidic soils, aluminium (Al) occurs as Al3+, which is phytotoxic. One of the most conspicuous symptoms of Al toxicity is the root growth inhibition, which can lead to low water uptake and consequent reduction in leaf hydration and gas exchange. However, fibrous xylem vessels have been observed in roots of 'Rangpur' lime plants (Citrus limonia L.) when exposed to Al, which could affect the functioning of aquaporins, ultimately reducing their expression. We confirmed a decrease of CO2 assimilation (A), stomatal conductance (gs), transpiration (E) and relative leaf water content (RWC) in 3-month-old C. limonia plants exposed to 1480 μM Al in nutrient solution for 90 days. The estimated hydraulic conductivity from soil to the leaf (KL) and leaf water potential (Ψw) also showed low values, although not consistently reduced over time of Al exposure. The relative expression of aquaporin genes belonging to PIP family (PIP1-1, PIP1-2 and PIP2) showed downregulation for ClPIP1-1 and ClPIP2 and upregulation for ClPIP1-2 in plants exposed to Al. Furthermore, ClPIP1-1 was positively correlated with A and gs in plants exposed to Al. Therefore, downregulation of ClPIP1-1 and ClPIP2 in roots of 'Rangpur' lime plants could be associated with the low leaf hydration of this species when exposed to Al.
Keywords: abiotic stress; Citrus limonia; PIP; qPCR; water relations